THE USE OF THE IRAMUTEQ SOFTWARE IN DATA ANALYSIS IN QUALITATIVE OR QUALI-QUANTI RESEARCH - Castro Neta, Abília Ana (2021)
This study aims to describe the use of the IRAMUTEQ software as a tool to support data processing in qualitative research (and/or quali-quanti). Although IRAMUTEQ guarantees accurate results, the use of the software does not replace the researcher's protagonism. It is highlighted, in this perspective, that all stages of the research require seriousness and knowledge of the object under investigation, which permeates the choice of approach, the coherent and consistent discussion with the literature and the quality of the instrument to conduct the interview in data collection, so that the preparation of the corpus allows a better processing and presentation of the results that are generated by the software. In this sense, the researcher continues to be the conductor of the research, and his role is valued by IRAMUTEQ, which allows the interpretation of results already processed with scientific rigor.